Effect of Guided Inquiry on Pre-Service Teachers’ Achievement and Retention in Photosynthesis - Kibirige, Israel (Universitas Islam Indonesia, 2026)
This study investigated the effect of Guided Inquiry (GI) on pre-service teachers' academic achievement and retention in photosynthesis. A quasi-experimental research design was used with 65 pre-service teachers, where 32 were assigned to the experimental group (EG) and 33 to the control group (CG). Data were collected using a Learners' Achievement Test and analysed using descriptive statistics: means and standard deviations, and inferential statistics, including T-tests and analysis of covariance (ANCOVA). Both groups completed a pretest, and no significant difference was recorded in prior knowledge (p > .05). Post-tests measured pre-service teachers' achievement and retention after teaching both groups. A T-tests showed that learners taught using GI scored significantly higher than those taught using Traditional Teaching (TT) (p < .05). ANCOVA, controlling pretest scores, confirmed a significant effect of the teaching approach on post-test achievements in favour of GI (p < .05). Differences between male and female achievements were not statistically significant (p > .05). The findings suggest that GI enhances conceptual understanding and retention in science education.